Modelling soil water retention to identify management influence on soil pore characteristics - SILVA,RODRIGO F. DA (2022)
Abstract The water retention curve is widely used in studies involving soil. The management systems directly influence soil structure by altering water retention dynamics. Several equations are used to adjust the retention of water in the soil, but most of the time, the choice of these models occurs in an arbitrary way. From this problem, it was proposed with the present study to relate the best mathematical model to water retention, taking into account the different management systems adopted, based on previously established adjustment criteria. For the accomplishment the study, a soil of caulinitic mineralogy and average texture was utilized. The treatments were area under native Cerrado (Savanna), eucalyptus plantation with six and twelve years of cultivation, pasture with two and six years of cultivation, conventional plantation with two and eight years of cultivation, no-till with three and six years of cultivation. From the adjustment criteria for non-linear models, it was found that the management influences the choice of the water retention model. It is possible to observe that the greatest divergences between the models occurred close to the soil saturation zone, and that the Fredlung-Xing model is more efficient in adjusting the water retention curve under conservationist management systems.